Association between HBV DNA Level and Intrahepatic HBcAg Protein Expression of Hepatocytes in Patients with Chronic Hepatitis B - Devy Serevina; Ening Krisnuhoni; Rino Alvani Gani (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2010)
Background: Correlation between serum Hepatitis B viral deoxyribonucleic acid (HBV DNA) and hepatitis B core antigen (HBcAg) protein expression in the liver regarding hepatitis B e-antigen (HBeAg) status have not been well studied. This study was aimed to demonstrate association between serum HBV DNA and HBeAg levels with HBcAg expressions in the liver. Method: A total of 55 naive chronic hepatitis B (CHB) patients were enrolled. All samples were tested for HBeAg serum by serological test enzyme-linked immunosorbent assay (ELISA) and HBV DNA was determined by polymerase chain reaction (PCR) HBsAg and HBcAg were evaluated immunohistochemically in the liver tissue Results: Of 55 patients, 44 (80%) were HBeAg positive and 11 (20%) were HBeAg negative. There was a positive correlation between serum HBV DNA and HBcAg expression in the nuclei (r: 0.383; p = 0.004). There was association between HBcAg expression in the nucleus and qualitative HBeAg (p = 0.017). Conclusion: In the patient with chronic HBV, there is a very significant positive correlation between the level of viral replication and HBcAg expression in the nucleus of hepatocytes. Moreover, there is association between HBcAg expression in the hepatocytes nucleus and HBeAg serum level. These finding lead to the proposition that nucleus localization of HBcAg protein function to amplify the pool of cccDNA in the replication cycle of HBV.. Keywords: HBV DNA, Imunohistochemistry, HBcAg